If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x+8)/(x-1)=6
We move all terms to the left:
(5x+8)/(x-1)-(6)=0
Domain of the equation: (x-1)!=0We multiply all the terms by the denominator
We move all terms containing x to the left, all other terms to the right
x!=1
x∈R
(5x+8)-6*(x-1)=0
We multiply parentheses
(5x+8)-6x+6=0
We get rid of parentheses
5x-6x+8+6=0
We add all the numbers together, and all the variables
-1x+14=0
We move all terms containing x to the left, all other terms to the right
-x=-14
x=-14/-1
x=+14
| 14-8x=42 | | -8w+4(w-5)=16 | | W=z+1 | | a+3/4=-1/4 | | 47=3v+8 | | S+4t= | | 0.4(f+9)=12 | | 4+n=3n | | 3z+18=2z/4 | | 2n+6=2(n+) | | 68=4x+8 | | x/7-4=-10 | | x+10+x+13=19 | | F=q+2 | | 3/4x(x+8)=9 | | 4x-3=2x/7+1 | | 4x-3=2x/7=1 | | -y^2-9y+15=29 | | 2x+3-4x-5=0 | | -x-2=9(2-3x)+6 | | -20-11c=2c+20-15c | | 3x-5=6x-65 | | p−1/4X3=−56 | | 125=-13x-122 | | 16t=4+17t | | p−14X3=−56 | | -8y+16=-15y+5y+20 | | 12x1/2=3 | | (X-2×(x+4=0 | | -4b=16-3b | | 43.76=9g+3.62 | | 3(x-0.50)=5.97 |